Cost Optimization for Transportation Using Linear Programming - LAKSHMI; M. Suresh (The journal of contemporary issues in business and government, 2017)
Transportation plays a vital role in every manufacturing industry as it is one of the major activities that binds the whole supply chain and accounts for customer satisfaction with the right delivery time. Hence, bringing in an optimized transport routing on the grounds of time taken and cost of transportation is very important. In this paper, a cost optimization model for transportation of goods of a flavors and fragrance company is presented. The problem was a linear programming problem and was solved using an EXCEL solver. A savings of Rs. 765,000 per annum was estimated comparing the cost of transportation in the new model to that of the previous model.